GAMBARAAN PERNIKAHAN DINI PADA REMAJA DI WILAYAH KERJA DESA KARYAWANGI KECAMATAN PARONGPONG KABUPATEN BANDUNG BARAT TAHUN 2019 - Iga Retia Mufti (Jurnal Kesehatan Rajawali, 2020)
Background: According to WHO and UNICEF One of the problems in Indonesia is early marriage which is done under the age of 18 years. Early marriage can be caused by many factors that influence one of them is the knowledge and education possessed by women who do early age. Research Objectives: To find out how the picture of early marriage to adolescents in the work area of ​​the village of Karyawangi, Parongpong Sub-district, West Bandung RegencyResearch Method: This research uses descriptive research with cross sectional design. The sampling technique uses random sampling with a total sample of 117 teenagers. Data collection instruments using a questionnaire. Univariate data analysis to see the distribution of frequency, knowledge and education.Results: It was found that some of the knowledge of adolescent marriages was lacking (80.2%) and some education of adolescents in the village of Karyawangi SMP (44.0%).Conclusion: The occurrence of early marriage in adolescents is partly due to the lack of knowledge about early Conclusion: The occurrence of early marriage in adolescents is partly due to the lack of knowledge about early marriage, and lack of education with the average education level is junior high. marriage, and lack of education with the average education level is junior high.